Role of occupational therapy in epilepsy patients after left temporal lobe surgery - Schwarz, Michael; Geismar, Lisa; Schneider, Katrin; Kasper, Burkhard; Walther, Katrin; Hamer, Hajo (British Journal of Occupational Therapy, 2022)
There is a relevant risk of psychosocial as well as cognitive impairments in epilepsy patients with resective surgery in the left temporal lobe. Surgery in the speech-dominant hemisphere can be associated with deterioration of speech related functions including verbal memory. There are only limited studies addressing the impact of occupational therapy in postoperative rehabilitation of epilepsy patients.Method: In this study, a mixed-methods design based on the grounded theory concept was administered. Seven patients with left temporal lobe epilepsy and a risk profile for postoperative cognitive decline were investigated over various time points. Neuropsychological assessments occurred before surgery, 1 week, 3 months, and 6 months postoperatively. According to our rehabilitation concept, every patient started occupational therapy 1 month before surgery. Therapy lasted for at least 6 months after surgery. For all patients, extensive qualitative interviews with the occupational therapists and anamnestic data were analyzed.Results: In all patients, postoperative psychosocial difficulties emerged. Language and memory tests showed a decline after 6 months specifically for name retrieval. Occupational therapy was adapted to find individual solutions for the patients problems and to implement effective coping strategies.Conclusion: Cognitive training lead to consistent improvements over time. The results show that occupational therapy can be an efficient tool in the treatment of psychosocial and cognitive impairments after epilepsy surgery.
CRIS-Team WoS Importer:2022-03-04